Civilizar a nação pela instrução pública: formação de professores e ensino primário no Pará (1891-1909) - COSTA, Edivando da Silva (Universidade Federal do Pará, 2016)
This paper discusses teacher training for primary education in Pará, during the early years of the republican regime. In this context, education, according to the political and intellectual republican authorities, it would be one of the mechanisms for building a society that was intended to: modern and civilized. Analyzes, thus, the formation of professors and teachers, social subjects that would be responsible for the education of future citizens of the country, as well as a bit of teaching in primary schools. It has been as a research focus on the education received in the Normal School of Belém do Pará, for the training of teachers, and also the training that they should pass on in schools to their students. We understand that this is a process in which were present different formations and resistance and conflict.